Research on Meshing Force of Harmonic Reducer based on No-load Backlash and Circumferential Meshing Stiffness - Ziying Wang; Qungui Du; Dongzhou Zheng; Yuhang Hu; Mengfei Liu; Longfeng Zhong (Jixie chuandong)
The meshing force distribution of the harmonic reducer has a great effect on its carrying capacity，transmission efficiency，transmission accuracy and service life. An analytical model based on no-load backlash and circumferential meshing stiffness is proposed to describe the meshing condition between flexible wheel and rigid wheel more accurately under load status. The no-load backlash in the assembled state is calculated by geometric method，and the circumferential meshing stiffness is obtained through establishing and analyzing the mechanical model of the flexspline under load. The distribution of meshing force under different load conditions is obtained by iterative solution based on the no-load backlash and the circumferential meshing stiffness matrix. A finite element model is established to verify the accuracy of the analytical model，and the results are basically consistent.